Primeira Notícia da Descoberta de Waimirita e Atroarita, Dois Novos Minerais na Mina de Pitinga, AM, Brasil - MINUZZI, ORLANDO RENATO RIGON; FERRON, JOSÉ MAXIMINO TADEU MIRRAS; BASTOS NETO, ARTUR CEZAR; PEREIRA, VITOR PAULO (Pesquisas em Geociências, 2003)
<!-- .p { text-align: justify; } --> Waimirite and Atroarite are associated with the core of the albite-granite from the Madeira Granite and occur in different places as thin veins. Waimirite is a yttrium fluoride that macroscopically form massive and white rounded aggregates. Atroarite is a alumino-fluoride and macroscopically form dark grey octahedral crystals. The DRX analyses confirm that they are new minerals.